Multivariate genomic analysis and optimal contributions selection predicts high genetic gains in cooking time, iron, zinc, and grain yield in common beans in East Africa. Issue 3 (26th October 2021) - Saradadevi, Renu; Mukankusi, Clare; Li, Li; Amongi, Winnyfred; Mbiu, Julius Peter; Raatz, Bodo; Ariza, Daniel; Beebe, Steve; Varshney, Rajeev K.; Huttner, Eric; Kinghorn, Brian; Banks, Robert; et al.
Abstract: Common bean ( Phaseolus vulgaris L.) is important in African diets for protein, iron (Fe), and zinc (Zn), but traditional cultivars have long cooking time (CKT), which increases the time, energy, and health costs of cooking. Genomic selection was used to predict genomic estimated breeding values (GEBV) for grain yield (GY), CKT, Fe, and Zn in an African bean panel of 358 genotypes in a two‐stage analysis. In Stage 1, best linear unbiased estimates (BLUE) for each trait were obtained from 898 genotypes across 33 field trials in East Africa. In Stage 2, BLUE in a training population of 141 genotypes were used in a multivariate genomic analysis with genome‐wide single nucleotide polymorphism data from the African bean panel. Moderate to high genomic heritability was found for GY (0.45 ± 0.10), CKT (0.50 ± 0.15), Fe (0.57 ± 0.12), and Zn (0.61 ± 0.13). There were significant favorable genetic correlations between Fe and Zn (0.91 ± 0.06), GY and Fe (0.66 ± 0.17), GY and Zn (0.44 ± 0.19), CKT and Fe (−0.57 ± 0.21), and CKT and Zn (−0.67 ± 0.20). Optimal contributions selection (OCS), based on economic index of weighted GEBV for each trait, was used to design crossing within four market groups relevant to East Africa. Progeny were predicted by OCS to increase in mean GY by 12.4%, decrease in mean CKT by 9.3%, and increase in mean Fe and Zn content by 6.9 and 4.6%, respectively, with low achieved coancestry of 0.032. Genomic selection with OCS will accelerate breeding of high‐yielding, biofortified, and rapid cooking African common bean cultivars. Core Ideas: Common bean varied in grain yield, cooking time, iron, and zinc in East African field trials. Significant genomic heritability was present for all traits in an African bean panel. Favorable genetic correlations were found between high grain yield and high iron and zinc. Favorable genetic correlations were found between short cooking time and high iron and zinc. High genetic gains were predicted with genomic selection and optimal contributions selection.